UV resonance Raman analysis of trishomocubane and diamondoid dimers - Meinke, Reinhard; Richter, Robert; Merli, Andrea; Fokin, Andrey A.; Koso, Tetyana V.; Rodionov, Vladimir N.; Schreiner, Peter R.; Thomsen, Christian; Maultzsch, Janina (Journal of Chemical Physics, 2014)
We present resonance Raman measurements of crystalline trishomocubane and diamantane dimers containing a C=C double bond. Raman spectra were recorded with excitation energies between 2.33 eV and 5.42 eV. The strongest enhancement is observed for the C=C stretch vibration and a bending mode involving the two carbon atoms of the C=C bond, corresponding to the B2g wagging mode of ethylene. This is associated with the localization of the π-HOMO and LUMO and the elongation of the C=C bond length and a pyramidalization of the two sp2-hybridized carbon atoms at the optical excitation. The observed Raman resonance energies of the trishomocubane and diamantane dimers are significantly lower than the HOMO-LUMO gaps of the corresponding unmodified diamondoids. © 2014 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-03-17